1997
DOI: 10.2307/421196
|View full text |Cite
|
Sign up to set email alerts
|

On the Decision Problem for Two-Variable First-Order Logic

Abstract: We identify the computational complexity of the satisfiability problem for FO2, the fragment of first-order logic consisting of all relational first-order sentences with at most two distinct variables. Although this fragment was shown to be decidable a long time ago, the computational complexity of its decision problem has not been pinpointed so far. In 1975 Mortimer proved that FO2 has the finite-model property, which means that if an FO2-sentence is satisiable, then it has a finite model. Moreover, Mortimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
246
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(248 citation statements)
references
References 43 publications
2
246
0
Order By: Relevance
“…The two-variable fragment of first-order logic (two-variable logic or FO 2 for short) is known to be reasonably expressive and its satisfiability and finite satisfiability problems are decidable [Mor75], in fact they are complete for NEXPTIME [GKV97]. Unfortunately many important properties, as for example transitivity, cannot be expressed in two-variable logic.…”
Section: A Note On Two-variable Logicmentioning
confidence: 99%
“…The two-variable fragment of first-order logic (two-variable logic or FO 2 for short) is known to be reasonably expressive and its satisfiability and finite satisfiability problems are decidable [Mor75], in fact they are complete for NEXPTIME [GKV97]. Unfortunately many important properties, as for example transitivity, cannot be expressed in two-variable logic.…”
Section: A Note On Two-variable Logicmentioning
confidence: 99%
“…These vectors will form a part of the certificate for ϕ, which we assemble in § 4.6. We remind the reader of the notions of profile and c-spectrum, established in § 4.1, as well as the matrix U relating them, and defined in (6).…”
Section: Clustersmentioning
confidence: 99%
“…The logic L 2 has the finite model property [18], and its satisfiability (= finite satisfiability) problem is NExpTime-complete [6]. The logic C 2 is expressive enough for the finite model property to fail; nevertheless, its satisfiability and finite satisfiability problems remain NExpTime-complete [7,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the translation of a knowledge base uses only variables x and y, and thus yields a formula in the two variable fragment of first-order logic, which is known to be decidable in non-deterministic exponential time [79]. Alternatively, we can use the fact that this translation uses quantification only in a restricted way, and therefore yields a formula in the guarded fragment [2], which is known to be decidable in deterministic exponential time [78].…”
Section: Dls and Predicate Logicmentioning
confidence: 99%
“…Highly optimized systems (FaCT, RACE, and DLP [95,80,133]) showed that tableau-based algorithms for expressive DLs led to a good practical behavior of the system even on (some) large knowledge bases. In this phase, the relationship to modal logics [57,147] and to decidable fragments of first-order logic [33,129,79,77,78] was also studied in more detail, and applications in databases (like schema reasoning, query optimization, and integration of databases) were investigated [45,47,51].…”
Section: Introductionmentioning
confidence: 99%